FPGA implementation of Kahan summation algorithm - Darshni, R (2018)
In this project, Kahan Summation Algorithm, and an improved version of it, Kahan- Babuska Algorithm have been implemented in an FPGA platform to increase the accuracy in basic floating-point computation The Kahan Summation Algorithm is a method to add floating point numbers in a way to reduce the accumulation of error. The designs are configurable to sum to 100 floating point numbers. There are two implementations of the Kahan Summation Algorithm design, a purely blocking mode, and a hybrid mode with pipelining. The Kahan-Babuska algorithm is implemented in blocking mode. The designs have also been compared with each other, along with software implementations to study the effectiveness of the implementation.